The mediating role of occupational commitment in the effects of work–family conflict on intention to leave - KOÇOĞLU SAZKAYA, MERVE (My University, 2023)
Introduction: It is important to increase the occupational commitment of nurses who experience work-family conflict to decrease their intention to leave. Aim: This study’s aim was to demonstrate the role of occupational commitment in the effects of work–family conflict on the turnover intention of nurses during the COVID-19 pandemic. Method: This descriptive study was conducted with 390 nurses working in two different hospitals of a foundation university in Istanbul. Results: The results of this study showed that there was an effect of work–family conflict on intention to leave (r2 = 0.19; p < 0.05) and occupational commitment (r2 = 0.01; p < 0.05). Another result of the research is that occupational commitment also affected the intention to leave (r2 = 0.24; p < 0.05). In addition, according to the results of the mediation analysis carried out to test the hypothesis of the research, there was a mediating effect of occupational commitment since the ꞵ coefficient of nurses' perceptions of work-family conflict in the first stage was 0.43, while it decreased to 0.40 in the third stage. This result showed that occupational commitment had a mediating role in the effects of work–family conflict on the intention to leave. Conclusion: This study showed that occupational commitment had a mediating role in the effects of work–family conflict on the intention to leave. According to the research results, although nurses experience work–family conflict due to working conditions during the COVID-19 pandemic, their occupational commitment decreases their intention to leave

Giriş: İş-aile çatışması yaşayan hemşirelerin işten ayrılma niyetlerini azaltmak için mesleki bağlılıklarını arttırmak önemlidir. Amaç: Bu çalışmanın amacı COVID-19 pandemi sürecinde hemşirelerin yaşamış oldukları iş-aile çatışmasının işten ayrılma niyetleri üzerindeki etkisinde mesleki bağlılığın rolünü belirlemektir. Yöntem: Bu çalışma tanımlayıcı bir araştırma olup, İstanbul'da bir vakıf üniversitesine ait iki farklı hastanede çalışan 390 hemşire ile yapıldı. Bulgular: Araştırma sonuçları, iş-aile çatışmasının işten ayrılma niyeti (r2 = 0,19; p < 0,05) ve mesleki bağlılık (r2 = 0,01; p < 0,05) üzerinde etkisi olduğunu gösterdi. Ayrıca mesleki bağlılığın işten ayrılma niyetini de etkilemesi araştırmanın bir diğer sonucudur (r2 = 0,24; p < 0,05). Bunun yanı sıra, araştırmanın hipotezini test etmek için yapılan aracılık analizi sonuçlarına göre hemşirelerin birinci aşamadaki iş-aile çatışması algıları β katsayısı 0,43 iken üçüncü aşamada 0,40’a anlamlı bir biçimde düşmesi nedeniyle mesleki bağlılığın kısmi aracılık etkisi söz konusudur. Bu sonuç, iş-aile çatışmasının işten ayrılma niyeti üzerindeki etkisinde mesleki bağlılık aracı rolü olduğu belirlendi. Sonuç: İş-aile çatışmasının işten ayrılma niyeti üzerindeki etkisinde mesleki bağlılığın aracılık rolüne sahip olması araştırmanın sonucudur. Bir başka ifadeyle, araştırmada hemşirelerin COVID-19 pandemi döneminde çalışma koşullarından kaynaklı iş-aile çatışması yaşamalarına rağmen sahip oldukları mesleki bağlılıkları onların işten ayrılma niyetlerini azalttığı görüldü.
İş-aile çatışmasının işten ayrılma niyeti üzerindeki etkisinde mesleki bağlılığın aracılık rolü
Keywords: COVID-19; family conflict; institutional adherence; nurses; Aile çatışması; kurumsal bağlılık; hemşireler